Puring Potensi Bioremediasi Tanaman Puring (Codiaeum variegatum) terhadap Pencemaran Timbal (Pb) di Jalan Raya: Studi Lapangan: Potensi Bioremediasi Tanaman Puring (Codiaeum variegatum) terhadap Pencemaran Timbal (Pb) di Jalan Raya: Studi Lapangan - ibnu rois; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2023)
Air pollution in urban areas is largely caused by motor vehicle emissions containing lead additives (Pb). One of these additives is tetraethyl lead (TEL) found in vehicle fuels, which produces fine lead particles (Pb). These lead particles are hazardous due to their very fine size, making them easily inhalable by humans. Continuous exposure to lead over time can have significant health impacts on humans. Reducing air pollution from lead particles can utilize the Croton plant because it possesses several advantages. This study aims to measure the ability of the Croton plant (Codiaeum variegatum) to absorb lead on the roadside using a pre-post test group design. Croton plants were cultivated in pots and exposed to lead-contaminated environments for 3 days. The analysis results showed a significant increase in lead concentrations in croton leaves at various plant heights (p < 0.05), with the highest concentration at 0.5 meters reaching 0.33 mg/Kg. The Croton plant has proven effective in absorbing lead without compromising its growth, supported by its strong adaptability, extensive root system, and leaves acting as biological filters. Based on these results, the Croton plant is highly suitable for use as both an ornamental plant and a bioremediation medium in urban areas contaminated with lead (Pb).